Azidoacetic Acid Amides in the Synthesis of Substituted Arylidene‐1‐H‐imidazol‐5‐(4H)‐ones. Issue 30 (8th August 2018) - Zaitseva, Snizhana O.; Golodukhina, Svetlana V.; Baleeva, Nadezhda S.; Levina, Evgenia A.; Smirnov, Alexander Yu.; Zagudaylova, Marina B.; Baranov, Mikhail S.
Abstract: We present a novel efficient method for the synthesis of substituted arylidene‐1‐ H ‐imidazol‐5‐(4 H )‐ones based on the use of azidoacetic acid amides. The proposed approach was successfully used for the preparation of three rows of target substances with different substituents in the imidazolone ring and benzylidene moiety. The presented methodology tends to be multipurpose and convenient for the introduction of substituents in any position. Abstract : We present a novel efficient method for the synthesis of substituted arylidene‐1‐ H ‐imidazol‐5‐(4 H )‐ones based on the use of azidoacetic acid amides. The proposed approach was successfully used for the preparation of three rows of target substances with different substituents in the imidazolone ring and benzylidene moiety. Presented methodology tends to be multipurpose and convenient for the introduction of substituents in any position.